Evaluation of new generation atmospheric dispersion models. (1st January 2002) - Hall, D.J.; Spanton, A.M.; Bennett, M.; Dunkerley, F.; Griffiths, R.F.; Fisher, B.E.A.; Timmis, R.J.
The paper considers the regulatory view of evaluating dispersion models. There is no proscription for regulatory studies in the UK, so differences between dispersion calculations from different models and versions of models are then as important as their absolute veracity. An example shows variations in calculated concentration due to variations between two different versions of a model and two different sources of meteorological data. A simple standard test protocol that will reveal such differences is being developed as part of a model inter-comparison exercise between the US-EPA ISC model, the US-EPA AERMOD model and the UK ADMS model, these being the models most likely to be used for regulatory applications in the UK.